Grounded Description - Barney G. Glaser (Grounded Theory Review: An International Journal)
Grounded description is on the increase with the increase of grounded theory throughout the world. Much grounded description is jargonized as GT and it is not GT. Grounded description is trying to describe the population studied, like a QDA study requires, by describing all the interchangeable indicators that grounded the concept. In contrast, GT is not to describe the population. GT is the relation between concepts which emerged from the population by constant comparing and then are related to each other by a theoretical code. The GT theory then becomes general and abstract of the study population by time, place and people. The GT stands on its own, and the data on which it is grounded is often forgotten for the grab and general implications of the theory.